Brain activation during anticipatory anxiety in social anxiety disorder - Böhme, Stephanie; Ritter, Viktoria; Tefikow, Susan; Stangier, Ulrich; Strauss, Bernhard; Miltner, Wolfgang H. R.; Straube, Thomas (Social cognitive and affective neuroscience, 2013)
Exaggerated anticipatory anxiety during expectation of performance-related situations is an important feature of the psychopathology of social anxiety disorder (SAD). The neural basis of anticipatory anxiety in SAD has not been investigated in controlled studies. The current study used functional magnetic resonance imaging (fMRI) to investigate the neural correlates during the anticipation of public and evaluated speaking vs a control condition in 17 SAD patients and 17 healthy control subjects. FMRI results show increased activation of the insula and decreased activation of the ventral striatum in SAD patients, compared to control subjects during anticipation of a speech vs the control condition. In addition, an activation of the amygdala in SAD patients during the first half of the anticipation phase in the speech condition was observed. Finally, the amount of anticipatory anxiety of SAD patients was negatively correlated to the activation of the ventral striatum. This suggests an association between incentive function, motivation and anticipatory anxiety when SAD patients expect a performance situation.
Created from Fastlane, Scopus look-up
Keywords: Amygdala; Anticipatory anxiety; FMRI; Insula; Social phobia; Ventral striatum